Predictors of whole exome sequencing in dystonic cerebral palsy and cerebral palsy-like disorders - Pavelekova, P; Necpal, J; Jech, R; Havrankova, P; Svantnerova, J; Jurkova, V; Gdovinova, Z; Lackova, A; Han, V; Winkelmann, J; Zech, M; Skorvanek, M (Parkinsonism & related disorders, 2023)
INTRODUCTION: Cerebral palsy (CP) is a group of permanent disorders attributed to non-progressive disturbances that occurred in the developing fetal or infant brain. Cerebral palsy-like (CP-like) disorders may clinically resemble CP but do not fulfill CP criteria and have often a progressive course and/or neurodevelopmental regression. To assess which patients with dystonic CP and dystonic CP-like disorder should undergo Whole Exome Sequencing (WES), we compared the rate of likely causative variants in individuals regarding their clinical picture, co-morbidities, and environmental risk factors. METHOD: Individuals with early onset neurodevelopmental disorder (ND) manifesting with dystonia as a core feature were divided into CP or CP-like cohorts based on their clinical picture and disease course. Detailed clinical picture, co-morbidities, and environmental risk factors including prematurity, asphyxia, SIRS, IRDS, and cerebral bleeding were evaluated. RESULTS: A total of 122 patients were included and divided into the CP group with 70 subjects (30 males; mean age 18y5m±16y6m, mean GMFCS score 3.3 ± 1.4), and the CP-like group with 52 subjects (29 males; mean age 17y7m±1y,6 m, mean GMFCS score 2,6 ± 1,5). The WES-based diagnosis was present in 19 (27.1%) CP patients and 30 CP-like patients (57.7%) with genetic conditions overlap in both groups. We found significant differences in diagnostic rate in CP individuals with vs. without risk factors (13.9% vs. 43.3%); Fisher's exact p = 0.0065. We did not observe the same tendency in CP-like (45.5% vs 58.5%); Fisher's exact p = 0.5. CONCLUSION: WES is a useful diagnostic method for patients with dystonic ND, regardless of their presentation as a CP or CP-like phenotype.
Keywords: Dystonia; sekvenování exomu; Cerebral palsy; mužské pohlaví; mozková obrna; Cerebral palsy-like; Exome Sequencing; mozek; dystonické poruchy; Dystonic cerebral palsy; dystonie; Whole exome sequencing; Brain; Humans; WES; Dystonic Disorders; Cerebral Palsy; lidé; Male